Efektywność systemu nadzoru wizyjnego w warunkach częstej zmiany sceny = The effectiveness of the video surveillance systems in conditions of frequent scene change - Popławski, Andrzej (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
Monitoring and video surveillance systems are increasingly used in IoT devices. Various compression techniques are used here, which contribute to the deterioration of image quality. This quality depends not only on the camera and compression technique used, but also on the content recorded by the camera. The article presents research on the coding efficiency of video surveillance system in the conditions of frequent scene change.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne